1991
DOI: 10.1111/j.1460-9568.1991.tb00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Influx Induced by Stimulation of ATP Receptors on Neurons Cultured from Rat Dorsal Root Ganglia

Abstract: A combination of microspectrofluorimetry and single cell voltage-clamp was used to examine the response to ATP of cultured neurons from rat dorsal root ganglia. ATP activated an inward current and a rise in internal calcium concentration that was dependent on the external calcium concentration and on the magnitude of the ATP-induced current response. The response was not affected by prerelease of internal calcium stores with caffeine. The rise in internal calcium was increased at hyperpolarized membrane potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…Consistent with this conclusion is the report that while mRNA for all P2x-purinoceptor subtypes can be detected in sensory neurones, the levels of the P2X3-subtype are much higher than the others (Chen et al, 1995). If this is mirrored at the level of protein expression, then the current carried by P2x3-purinceptors is likely to be the major component of current activated by ATP. The rapid desensitization of the currents seen in this study is very different from previous reports on neurones of the rat dorsal root ganglia (Bean, 1990;Bouvier et al, 1991) and nodose ganglia (Krishtal et al, 1983;Li et al, 1993;Khakh et al, 1995a), where the currents decayed over at least several seconds. It has been suggested that these slow currents may be due to the formation of a novel channel phenotype following heteropolymerization of P2x2-and P2x3-subunits .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Consistent with this conclusion is the report that while mRNA for all P2x-purinoceptor subtypes can be detected in sensory neurones, the levels of the P2X3-subtype are much higher than the others (Chen et al, 1995). If this is mirrored at the level of protein expression, then the current carried by P2x3-purinceptors is likely to be the major component of current activated by ATP. The rapid desensitization of the currents seen in this study is very different from previous reports on neurones of the rat dorsal root ganglia (Bean, 1990;Bouvier et al, 1991) and nodose ganglia (Krishtal et al, 1983;Li et al, 1993;Khakh et al, 1995a), where the currents decayed over at least several seconds. It has been suggested that these slow currents may be due to the formation of a novel channel phenotype following heteropolymerization of P2x2-and P2x3-subunits .…”
Section: Discussioncontrasting
confidence: 99%
“…The aim of this study was to characterize the pharmacological and biophysical properties of the P2x-purinoceptor(s) present in neurones of the rat dorsal root ganglia. These cells have previously been shown to respond to ATP with a rapidly developing inward current (Bean, 1990;Bouvier et al, 1991), but it is not known which subtype(s) of P2x-purinoceptor they functionally express. A preliminary account of these results has been published (Roberston et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A relatively high permeability of ATP‐activated cation channels to Ca 2+ was found in rat pheochromocytoma cells (PC12) (Nakazawa et al , 1990), nucleus tractus solitarii neurons (Ueno et al , 1992) and human embryonic kidney (HEK 293) cells with exogenously transfected P2X receptors under the voltage‐clamp condition (Evans et al , 1996). Fura‐2 fluorescence recording also showed that ATP causes a rise in intracellular Ca 2+ ([Ca 2+ ] i ) associated with catecholamine release in PC12 cells (Nakazawa & Inoue, 1992) and [Ca 2+ ] i influx into rat cultured DRG neurons through a P2X receptor channel complex (Bouvier et al , 1991). There is increasing evidence that Ca 2+ influx through the P2X receptor plays an important role in the modulation of this receptor type (Burnstock & Wood, 1996; Khiroug et al , 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The cell body diameters ranged between 10 and 25 μm and ∼90% of the cells had two or more, short‐ or medium‐sized processes. We then examined their responsiveness to bath applications of capsaicin which acts selectively on sensory neurones (Bevan & Szolcsanyi, 1990) and α,β‐methylene adenosine‐triphosphate, an agonist at purinergic receptors (Bouvier et al ., 1991).…”
Section: Resultsmentioning
confidence: 99%